Influence of Glass Fiber Content on Sintering of Construction and Demolition Waste to Manufacture Ceramic Parts - José Carlos Rebollo-Alburquerque; Jesús Iñaki Gómez-Domínguez; María Natividad Antón Iglesias (Ceramics)
The present work aims to determine the possibility of using construction and demolition waste (CDW) and wind turbine blade waste (WTBW) together for the fabrication of sintered specimens using only waste materials. The sinterability curve was determined for five compositions with different amounts of WTBW (from 10 to 50% in mass). The materials were characterized by optical and electronic microscopy and X-ray diffraction. Later, the series was mechanically characterized by the application of the Brazilian test. The obtained tensile strength values were approximately 12 MPa, which were sufficient for their utilization as building materials; however, the composition with more WTBW was problematic due to the deformation in the specimens, which was the main effect of the addition of a larger amount of WTBW.